Tradisi dan transformasi sejarah Sunda - Lubis, Nina H. (Nina Herlina), 1956- (Bandung : Humaniora Utama Press, 2000)
Sundanese history in West Java, Indonesia.
'Haruskah Banten berpisah dari Jawa Barat?': Cover.
Includes bibliographical references (p. 247-254) and index.
Keywords: Sundanese (Indonesian people) -- History; Jawa Barat (Indonesia) -- History